Experimental Validation of a Numerical Model to Predict the Performance of Solar PV Cells - Asim, Muhammad; Usman, Muhammad; Hussain, Jafar; Farooq, Muhammad; Naseer, Muhammad Irfan; Fouad, Yasser; Mujtaba, M.A.; Almehmadi, Fahad Awjah (Frontiers in Energy Research, 2022)
The models designed for evaluation the performance of photovoltaic (PV) cells depends on classical thermal principles with the use of constant optical coefﬁcients (reﬂectance, absorbance and transmittance). However, these optical coefﬁcients depend on the incident angle actually and hence, are a function of the inclination and orientation of PV panel along with the geographical location and time of the day. In this paper, we considered the varying coefficients (optical thermal model) and the constant coefficient (classical thermal model) with incident angle in the energy balance equations followed by experimental validation. For Numerical modelling of Solar PV system installed in Jhang District of Punjab, MATLAB was used. At first, the incident angle of direct radiation on PV panel was determined with the help of astronomic simplified calculations and secondly, the optical coefﬁcients were evaluated by using the principles of classical electromagnetic theory. Thirdly, the energy balance equations are expressed in the form of differential equations and are solved numerically by Runge–Kutta method to get the electrical power as a function of time. Finally, the electrical power produced by the optical–thermal model (varying optical coefficient depending upon incident angle) and classical thermal model (constant optical coefficients) was validated by experimentally for solar PV system installed at Central Station, Punjab Emergency Service. The results showed signiﬁcant agreement between classical thermal model and experimentally produced electricity throughout the year which validates the modelling.